Efektivitas Model Pembelajaran Project Based Learning terhadap Kemampuan Menulis Kreatif Teks Editorial Bahasa Indonesia - Uswatun Hasanah; Muhammad Saleh (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Effectiveness of Project Based Learning Model on Creative Writing Ability of Indonesian Editorial Texts. This research is motivated by the problems that occur among students, namely the lack of student writing skills due to the fact that students are not given learning methods that are in accordance with the editorial text material being studied. The purpose of the study is to determine the level of student mastery in the Project Based Learning learning model and its relationship with writing creative editorial texts. This research uses a descriptive approach and is in the form of qualitative research. Learning to write creative editorial texts with a project-based learning model succeeded in improving students' learning scores. It shows a significant improvement compared to the previous learning results in writing creative editorial text. So that satisfactory results were obtained from the application of the Project Based Learning model in editorial text learning with the average value before application was 77, and the value after application increased to 90.